Integrasi ‘Laudato SI’ Dalam Program Pengabdian Masyarakat: Upaya Mewujudkan Green Campus di Kampus BSD UNIKA ATMA JAYA - Maria Magdalena Wahyuni Inderawati; Yasinta Ratna Esti Wulandari; Herman Yosep Sutarno; Anastasia Tatik Hartanti; Titis Puspitarini; Ronald Sukwadi (LPPM Universitas HKBP Nommensen, 2025)
This article presents a Community Service Program conducted at the BSD Campus of Unika Atma Jaya, focusing on the integrated implementation of sustainability based on Laudato Si. The activities aim to preserve the environment, particularly the campus lake, and to internalize the values of Laudato Si among the entire academic community. The methods employed involve the engagement of students, staff, and the surrounding community in the Eco Enzyme Festival 2024, which is also part of the effort to break a MURI record. This initiative produced 50 liters of eco-enzyme used to maintain the lake's ecosystem quality. Additionally, the program includes education on waste management and environmental conservation. With active participation from various stakeholders, it is hoped that this initiative will enhance awareness and tangible actions in sustaining the environment at the BSD Campus.